The Prognostic Impact of Lymph Node Dissection on Primary Tumor Resection for Stage IV Non–Small Cell Lung Cancer: A Population-Based Study - Zhang, Yudong; Zhang, Yichi; Cheng, Xinxin; Dai, Keyao; Xu, Bo; Liang, Shujun; Chen, Minsheng; Zhang, Honglang; Chen, Zhenguang (Frontiers in Oncology, 2022)
Objective: Selected stage IV non-small cell lung cancer (NSCLC) patients who underwent primary tumor resection have witnessed a survival benefit. Whether additional lymph node dissection (LND) would result in a better effect remain unknown. We investigated the prognostic impact of LND on stage IV NSCLC patients who received PTR. Methods: Patients with stage IV NSCLC who underwent primary tumor resection were identified from the Surveillance, Epidemiology and End Results database from 2004 to 2016. Propensity-score matching was performed to minimize the confounding effect, and lung cancer-specific survival (CSS) and overall survival (OS) were compared after matching. Multivariable Cox regression was used to identify prognostic factors and to adjust for covariates in subgroup analysis. The effect of the number of lymph nodes examined on the CSS was evaluated by repeating the Cox analysis in a binary method. Results: A total of 4,114 patients with stage IV NSCLC who receive surgery met our criteria, of which 2,622 (63.73%) underwent LND, and 628 patients were identified 1:1 in LND and non-LND groups after matching. Compared to the non-LND group, the LND group had a longer CSS (median: 23 vs. 16 months, p<0.001) and OS (median: 21 vs. 15 months, p<0.001). Multivariable regression showed that LND was independently associated with favorable CCS (HR=0.78, 95% CI 0.69-0.89, P<0.001) and OS (HR=0.79, 95% CI 0.70-0.89, P<0.001). Subgroup analysis suggested LND is an independent favorable predictor to survival in the surgical patients who were older age ( >60 years old), female, T3-4, N0, and M1a stage, and those who underwent sublobar resection. In addition, a statistically significant CCS benefit was associated with an increasing number of lymph nodes examined through 25 lymph nodes. Conclusions: LND with a certain range of lymph nodes number examined was associated with improved survival for stage IV NSCLC patients who received primary tumor resection. The results may have implications for guidelines on lymph nodes management in selective advanced NSCLC for surgery.